The Identity of Modern Muslim Women on Instagram: Studi Fenomenologi tentang Konstruksi Makna Hijab Terhadap Mikro Selebriti - Evie Ariadne Shinta Dewi; Tarisa Khairina Yunizar; Ikhsan Fuady (Universitas Negeri Jakarta, 2024)
This research aims to uncover the meaning of modern Muslimah identity, which is constructed by micro-celebrities through their accounts on social media such as Instagram. In addition, it also explores the motives that underlie a person to become a celebrity on Instagram. Using a phenomenological approach, data was collected through in-depth interviews with five informants, in addition to literature review and observation. The results revealed that the meaning of Muslimah identity is constructed by Instagram celebrities in three categories, namely: (1) The assertion of the definition of Muslimah is a Muslim woman who follows Islamic law, uses clothing as a cover for the aurat in accordance with Islamic law, the uploaded content displays positive content and does not expose the aurat, and in terms of endorsement, selecting the products received so as not to deviate from Islamic teachings becomes a necessity. (2) The motives of Muslimah celebgrams are divided into two, namely the motive of using Muslimah symbols and the motive of becoming a Muslimah celebgram on Instagram. In using Muslim symbols in the form of hijab, the motive is divided into two, namely the motive of cause and the motive of purpose. (3) Cause motives consists of fulfilling obligations as a Muslimah, encouragement from the family, and encouragement from the environment. The purpose motive consists of fulfilling religious obligations, protecting oneself, breaking the bad stigma against Muslim women, inspiring others, and improving oneself.